Occupational Army in Lithuania in 1990–1991: Problems and Solutions - Kšanytė, Raminta (Genocidas ir rezistencija, 2003)
The article gives analysis of attempts made in 1990–1991 to find solutions to the problems regarding presence and status of the occupational army of the Soviet Union. It gives deeper insight into how implemented were the main principles of the international law, what provisions in reference to the occupational army were formulated, and how performed was the search for possibilities to start withdrawal of the foreign army. To do this research, there were used the documents stored within the archives of the Chancellery of the Lithuanian Government, of the Lithuanian Parliament and Ministry of Foreign Affairs.